Answer:
√ x 12 = x 6 (or possibly − x 6 if you want to include the non-principal square root)
Answer:
a2 – b2 = (a – b)(a + b)
(a + b)2 = a2 + 2ab + b2
a2 + b2 = (a + b)2 – 2ab
(a – b)2 = a2 – 2ab + b2
(a + b + c)2 = a2 + b2 + c2 + 2ab + 2bc + 2ca
(a – b – c)2 = a2 + b2 + c2 – 2ab + 2bc – 2ca
(a + b)3 = a3 + 3a2b + 3ab2 + b3 ; (a + b)3 = a3 + b3 + 3ab(a + b)
(a – b)3 = a3 – 3a2b + 3ab2 – b3 = a3 – b3 – 3ab(a – b)
a3 – b3 = (a – b)(a2 + ab + b2)
a3 + b3 = (a + b)(a2 – ab + b2)
(a + b)4 = a4 + 4a3b + 6a2b2 + 4ab3 + b4
(a – b)4 = a4 – 4a3b + 6a2b2 – 4ab3 + b4
a4 – b4 = (a – b)(a + b)(a2 + b2)
a5 – b5 = (a – b)(a4 + a3b + a2b2 + ab3 + b4
Answer:
^G=98°
Step-by-step explanation:
So you know that angle x and angle g summed up together make 180°.
^F+^H+^G= 180°
<=> 53°+45°+^G=180°
<=> ^G= 180°-98°=82°
180°-82°=98°
Answer:
1. 244
2. 122
3. 61
Step-by-step explanation:
1. 244 because I divided 488 by 2.
2. Divide 244 by 2.
2. Divide 122 by 2.